2022
DOI: 10.31083/j.rcm2306184
|View full text |Cite
|
Sign up to set email alerts
|

TakoTsubo Syndrome: A Well-Known Disease but Not Everything Is Clear Yet

Abstract: TakoTsubo Syndrome (TTS) is a stress-induced cardiac disease characterized by temporary and segmental left ventricle dysfunction, typically involving the apex. Post-menopause women are more frequently affected. ECG and clinical features at presentation may be similar to those observed in acute coronary syndrome (ACS). However underlying pathomechanisms are completely different and, for what concerns TTS, extremely debated and not yet completely understood. Some hypotheses have been proposed during years, mostl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Additionally, catecholamines like adrenaline or dobutamine actually cause vasodilation in coronary arteries, and preclinical models have shown that inducing TTS with catecholamines in the absence of endothelin can lead to apical dysfunction [26] without any abnormality in myocardial perfusion. However, secondary TTS can also occur in patients with mildly-obstructive CAD, who are more likely to have in-hospital complications and recurrences overtime [27]. In addition to the initial contractile dysfunction seen in TTS, it seems that long-term effects of high adrenaline may involve cardiac inflammation.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Additionally, catecholamines like adrenaline or dobutamine actually cause vasodilation in coronary arteries, and preclinical models have shown that inducing TTS with catecholamines in the absence of endothelin can lead to apical dysfunction [26] without any abnormality in myocardial perfusion. However, secondary TTS can also occur in patients with mildly-obstructive CAD, who are more likely to have in-hospital complications and recurrences overtime [27]. In addition to the initial contractile dysfunction seen in TTS, it seems that long-term effects of high adrenaline may involve cardiac inflammation.…”
Section: Pathophysiologymentioning
confidence: 99%
“…10 , 11 Current international experts agree 11 about the common terminology of TS, although some aspects remain to be elucidated. 12 …”
Section: Takotsubo (蛸 壺 In Japanese) Syndromementioning
confidence: 99%